Comparative studies for failure pressure prediction of corroded pipelines. (November 2017) - Motta, Renato S.; Cabral, Hélder L.D.; Afonso, Silvana M.B.; Willmersdorf, Ramiro B.; Bouchonneau, Nadège; Lyra, Paulo R.M.; de Andrade, Edmundo Q.
Abstract: The Finite Element (FE) Method is one of the most efficient approaches to quantify reliably the remaining strength of corroded pipes, by allowing the direct simulation of the physical phenomena involved in the failure of the pipe. In this paper, the results of failure pressure of corroded pipelines obtained using nonlinear FE analyses of the models generated by a computer system called PIPEFLAW will be presented. This system integrates several tools to automatically generate FE models and to perform FE analysis using a friendly interface. A set of cases considering colonies of idealized corroded defects is analyzed. The results are compared to experimental burst tests presented in the literature, numerical results obtained via FE models generated manually and results obtained using semi-empirical methods. The results obtained using the PIPEFLAW automatic and flexible procedures show good agreement with those given by handmade FE models and experimental tests. Some highly conservative predictions given by the semi-empirical methods are also observed. Graphical abstract: Highlights: We describe semi-empirical methods to evaluate corroded pipe structural integrity. We describe operation conditions used by the program to perform numerical analysis. Some study cases of pipe models with idealized corrosion defects are presented. Semi-empirical, experimental and numerical results are presented and discussed.